2017
DOI: 10.3892/or.2017.5582
|View full text |Cite
|
Sign up to set email alerts
|

Effective cytotoxic activity of OSW-1 on colon cancer by inducing apoptosis in vitro and in vivo

Abstract: Abstract. As a natural compound, Ornithogalum caudatumAit is primarily used as an anti-inflammatory and antitumor agent in Chinese folk medicine. In 1992, OSW-1 was isolated from this compound, which is a new member of cholestane saponin family. In numerous recent studies, OSW-1 has been shown to have powerful cytotoxic anticancer effects against various malignant cells. However, the therapeutic efficacy of OSW-1 on colon cancer and the underlying mechanism are not understood. To explore the mechanism underlyi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 52 publications
1
30
0
Order By: Relevance
“…The p62 protein is involved in the lysosome-dependent degradation system that directly interacts with LC3-II and degradation in the process of autophagy, and suppression of autophagy results in enhanced p62 protein levels [ 44 , 61 ]. Accumulating evidence suggested the dual effect of autophagy on cancer, contributing to cell death or protecting cell survival [ 31 , 33 35 ]. In our study, we found that ACT induced autophagy dose-dependently, which was proved by the accumulation of autophagic vesicles and improvement of LC3B-I/II and Beclin 1, as well as reduction of p62.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The p62 protein is involved in the lysosome-dependent degradation system that directly interacts with LC3-II and degradation in the process of autophagy, and suppression of autophagy results in enhanced p62 protein levels [ 44 , 61 ]. Accumulating evidence suggested the dual effect of autophagy on cancer, contributing to cell death or protecting cell survival [ 31 , 33 35 ]. In our study, we found that ACT induced autophagy dose-dependently, which was proved by the accumulation of autophagic vesicles and improvement of LC3B-I/II and Beclin 1, as well as reduction of p62.…”
Section: Discussionmentioning
confidence: 99%
“…Induction of apoptosis presents an essential mechanism for drug-exploration against various cancers [ 34 ]. In general, there are two main apoptotic pathways: the intrinsic and the extrinsic [ 35 ]. The two pathways converge on the activation of Caspases, which contain a family of cysteine proteases and play an essential role in the completion of apoptosis [ 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…Comprehensive proteomics revealed the global protein changes and Paris polyphylla Smith var. yunnanensis (polyphyllin I) Osteosarcoma UPR and ER stress [8,9] Salvia miltiorrhiza (tanshinone IIA) Osteosarcoma Bcl-2 regulation [10] Cervical cancer ER stress [11] Epimedium (icaritin) Cervical cancer ROS stress [12] Chinese bayberry (flavonoids) Ovarian cancer Bcl-2 regulation [13] Psoralea corylifolia Breast cancer Bcl-2 regulation [14] Pueraria (6″-O-xyloside) Colon cancer Bcl-2 regulation [16] Ornithogalum caudatum Ait (OSW-1) Colon cancer Cytochrome c release [17] Ginkgo biloba (ginkgolic acids) Colon cancer ROS stress [18] Macleaya cordata (sanguinarine) Colorectal cancer Bax regulation [20] Cordyceps sinensis (cordycepin) Pancreatic cancer Bcl-2 regulation [22] Angelica sinensis (N-butylidenephthalide) Gastric cancer MMP [23] Lonicera japonica (luteolin) the network analysis confirming that Tan IIA administration activated ER stress signaling cascade that eventually resulted in mitochondrial-related apoptosis [11]. Cervical cancer is the fourth most common female malignancy in the world.…”
Section: Chinese Herbal Medicine That Induces Intrinsic Apoptosis In mentioning
confidence: 99%
“…As a natural compound, Ornithogalum caudatum Ait is primarily used as an anti-inflammatory and antitumor agent in Chinese folk medicine. It was shown that with low toxicity on normal colonic cells, an isolated compound OSW-1 suppressed colon cancer cells in vitro via intrinsic apoptotic pathway, whereby it increased cellular calcium, changed mitochondrial membrane potential, disrupted mitochondrial morphology, and led to the release of cytochrome c and the activation of caspase-3 [17]. Ginkgolic acids (GA), a botanical drug extracted from the seed coat of Ginkgo biloba L., possess various bioactive properties.…”
Section: Chinese Herbal Medicine That Induces Intrinsic Apoptosis In mentioning
confidence: 99%
“…Other authors have also emphasized that extracts or components obtained from various Ornithogalum species may exhibit cytotoxic effects on cancer cells [10][11][12][13] . Iguchi et al, Zhang et al, and Koyuncu et al recently predicted that plants from the genus Ornithogalum may represent important sources as anticancer agents [14][15][16][17] . This study employed the colorimetric MTT method to investigate the cytotoxic and antiproliferative effects of methanol (MeOH) and ethyl acetate (EtOAc) extracts from O. balansae flowers and bulbs on A549, CRL-2923, HT-29 and HeLa cell lines and the normal ARPE-19 cells.…”
mentioning
confidence: 99%